Dampak Kebijakan Status Dosen Terhadap Kinerja Dosen Perguruan Tinggi Swasta Di Bandar Lampung - Zuriana Zuriana; Besti Lilyana; Herlina Herlina (Program Pascasarjana Universitas Gajayana, 2019)
Lecturers as instructors as well as educators are one of the components of PT that can form hardskills and soft skills from every student. Tridharma which is carried out by the lecturer is a form of lecturer performance to the DIKTI. In the performance of lecturers performance is regulated by Republic of Indonesia Minister of Education and Culture Regulation No. 84 of 2013, Republic of Indonesia Minister of Education and Culture Regulation No. 84 of 2013, Minister of Education and Culture Decree No.062/O/1982, No.0135/O/1990 and Minister of Education Decree No.184/U/2001. In the implementation of tri dharma lecturers are inseparable from students in their respective universities. Seeing this, the lecturer / student ratio is ≥ 100 for study programs that have a 1:30 IPA lecturer/student ratio and 1:45 IPS. The problem polemic is that the permanent lecturer and homebase status both have NIDN, lecturer lecturers do not have NIDK, extraordinary lecturers or non-permanent lecturers do not have NUP, different working hours, teaching with cut loads, guiding and testing (these are only a few colleges the only level that applies to homebase lecturers), academic supervisors, while for research and service are made the same. If viewed from the regulation of the Minister of Research, Technology and Higher Education of the Republic of Indonesia number 26 of 2015 concerning the status of lecturers in Higher Education based on NIDN, NIDK; and this NUP violates but this is made to complete the ratio of lecturers and students as well as each lecturer can implement tri dharma in the field of research and service to the rules in simlibtamas. the type of research that will be conducted is quantitative research, the research method used is descriptive research. The type of data used is primary data and data collection techniques, namely the interview method. From the results of the validity test all produce valid, descriptive tests produce 100% and the results of SEM data processing result in a lecturer status policy significantly influencing the performance of the lecturer.